RARE EARTH ELEMENT INVERSION FOR MELT DISTRIBUTION: SENSITIVITY AND APPLICATION - Brodie Ja.; Latin D.; White N. (My University, 1994)
Inversion of rare earth element (REE) abundances in MgO-rich (MgO ~6 wt.%) igneous rocks, described initially by McKenzie & ONions (1991), provides a useful means of constraining the distribution of melt fraction with depth, X(z), in the mantle. Here, we investigate the sensitivity of the REE inversion procedure to noise in measured REE abundances and to variation in parameters which must be specified a priori. Inverted melt distributions are insensitive to realistic amounts of random noise but are sensitive to systematic noise. Melt distributions are also sensitive to input parameters such as depth and range of melting, source composition, and mantle mineralogy. To determine unique melt distributions, additional independent constraints on at least two of the following input parameters are therefore required: depth and range of melting (i.e., lithospheric thickness); source composition; source mineralogy (dependent on mantle temperature). The successful replication of melt compositions where these three parameters are well constrained and the agreement between inverted melt distributions and melt distributions calculated independently assuming isentropic melting during adiabatic upwelling indicate that the scheme is reliable. REE inversion therefore provides a means for both routinely constraining X(z) and for determining unknown input parameters.